2009
DOI: 10.1051/0004-6361/200810744
|View full text |Cite
|
Sign up to set email alerts
|

Detailed radio to softγ-ray studies of the 2005 outburst of the new X-ray transient XTE J1818-245

Abstract: Context. XTE J1818−245 is an X-ray nova that experienced an outburst in 2005, as first seen by the RXTE satellite. The source was observed simultaneously at various wavelengths up to soft γ-rays with the INTEGRAL satellite, from 2005 February to September, during our INTEGRAL Target of Opportunity program dedicated to new X-ray novae and during Galactic Bulge observations. Aims. X-ray novae are extreme systems that often harbor a black hole, and are known to emit throughout the electromagnetic spectrum when in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 55 publications
1
2
0
Order By: Relevance
“…Steeghs et al (2005a) observed it a few days after the outburst and detected an optical candidate counterpart with R ∼ 17.71 mag which was later confirmed by Zurita Heras et al (2011). We observed this source a month after the outburst discovery and detected a NIR counterpart with an apparent magnitude of Ks = 16.18 ± 0.02; this is consistent with the result from Cadolle Bel et al (2009). They observed XTE J1818-245 in the NIR two months after the outburst start and detected a counterpart with apparent magnitude K = 16.9 ± 0.2.…”
Section: Xte J1818-245supporting
confidence: 90%
“…Steeghs et al (2005a) observed it a few days after the outburst and detected an optical candidate counterpart with R ∼ 17.71 mag which was later confirmed by Zurita Heras et al (2011). We observed this source a month after the outburst discovery and detected a NIR counterpart with an apparent magnitude of Ks = 16.18 ± 0.02; this is consistent with the result from Cadolle Bel et al (2009). They observed XTE J1818-245 in the NIR two months after the outburst start and detected a counterpart with apparent magnitude K = 16.9 ± 0.2.…”
Section: Xte J1818-245supporting
confidence: 90%
“… 1 Wu et al (2010); 2 Deegan et al (2009); 3 Taam et al (1997); 4 Revnivtsev et al (2000); 5 Homan et al (2001); 6 Tanaka & Shibazaki (1996); 7 van der Hooft et al (1999); 8 Harmon et al (1995); 9 Gliozzi et al (2010); 10 in't Zand et al (1992); 11 Trudolyubov et al (1996); 12 Motta, Munoz‐Darias & Belloni (2010); 13 Garcia et al (2010); 14 Esin et al (2000); 15 Cadolle Bel et al (2009); 16 Corbel et al (2004); 17 Soleri et al (2008); 18 Tomsick et al (2003); 19 Belloni et al (2000); 20 Kitamoto et al (1990); 21 Casares et al (2004); 22 Sobczak et al (2000); 23 Hynes et al (2003); 24 Miller et al 2004; 25 Shrader et al (1997); 26 van Paradijs (1996); 27 Kolb et al (1997); 28 Buxton & Bailyn (2004) 29 Życki, Done & Smith (1997); 30 Życki et al (1999); 31 Zhang et al (2007); 32 Greiner et al (1994); 33 Brocksopp et al (2001); 34 Cui et al (1999); 35 Sobczak et al (1999). …”
Section: Observational Constraintsmentioning
confidence: 99%
“…They detected a new optical source with a magnitude of R ∼ 17.5 mag during their 1‐h observation that started on 2005 August 17 at 23:19 ut . Multiwavelength (from radio to soft γ‐rays) observations performed from August to September, searching for the nature of XTE J1818−245 and modelling its hard X‐rays, are extensively described in a companion paper (Cadolle Bel et al 2009, hereafter Paper I). This new X‐ray transient source is probably a low‐mass X‐ray binary and a black hole candidate, located closer to us than the Galactic Centre (Paper I).…”
Section: Introductionmentioning
confidence: 99%